Organization of fine root data obtained from minirhizotrons and ingrowth soil cores (how to construct an operational database using MS Access) - Železnik, Peter (Zbornik gozdarstva in lesarstva, 2011)
Root observation with minirhizotrons is a useful technique to study root system dynamics by means of a transparent tube and a root image acquisition device. It has been in use in root studies for a few decades. The method is best complemented by sequential soil coring for studying root growth in defined soil volume in a time sequence of sampling, or by use of ingrowth soilcores method, which allows measurement of fine root biomass and growth in the exposed soil (substrate) cores during a defined time interval. Most fine root studies techniques are based on picture taking and computerized image analysis. From such analyses, enormous amount of raw data is derived, which ishard to control and manipulate. To enable a friendly and reliable data organization, two MS Access databases were designed, using data from minirhizotron pictures and ingrowth soil cores. These MS Access databases enable the data user to save time and reduce the amount of errors made during data handling (such as extensive copy-paste data routines in and out of numerous Excel files). Our aim was to improve data quality control and allow an easy, friendly and efficient way of manipulation of fine root growth data without a high level of knowledge on database construction. Therefore, in thisstudy, we present an efficient way of handling a large amount of minirhizotron and ingrowth soil cores data, by using MS Access database. To better present the protocols some results and experience on improving data quality are presented.
Keywords: korenine; minirizotroni; rast korenin